Alpheus formosus Gibbes 1850 - Anker, Arthur; Hurt, Carla; Knowlton, Nancy (Zenodo, 2008)
Alpheus formosus Gibbes, 1850 Figs. 1 –4, 7 c–e Alpheus formosus Gibbes 1850: 196; Kingsley 1878 a: 190; Heilprin 1888: 322; Heilprin 1889: 151; Coutière 1899 (for page numbers see Chace & Forest 1970); Coutière 1910: 485; Verrill 1900: 579; Rathbun 1900: 152; Rathbun 1901: 106; Verrill 1922: 84; Balss 1924: 177; Boone 1930: 166; Chace 1956: 146; Hazlett 1962: 82; Bullis & Thompson 1965: 8; Wiliams 1965: 64; Fausto-Filho 1970: 56; Hendrix 1971: 83; Chace 1972: 67; Corrêa 1972: 3; Coelho & Ramos 1972: 148; Ray 1974: 104; Abele 1976: 273; Camp et al . 1977: 25; Gore et al . 1978: 225; Christoffersen 1979: 314 (part.); Corredor et al . 1979: 32; Christoffersen 1980 a: 65; Christoffersen 1980 b: 39; Rodríguez 1980: 145; Fausto-Filho 1980: 113; Morgado 1980: 33; Reed et al . 1982: 768; Carvacho 1982: 18; Cubit & Williams 1983: 24; Williams 1984: 94; Lemaitre 1984: 426; Young 1984: 29; Freitas-Lins 1985: 39; Young 1986: 106; Sterrer 1986: 325; Rodríguez 1986: 143; Abele & Kim 1986: 197, 206; Kim & Abele 1988: 39, 40; Márquez 1988: 34; Markham et al . 1990: 421; Martínez-Iglesias et al . 1996: 33; Hernández Aguilera et al. 1996: 32; Martínez-Iglesias et al . 1997: 423; Hobbs 1998: 906; Santos & Coelho 1998: 73; Posey et al . 1998: 154; Christoffersen 1998: 358; Vargas & Cortés 1999: 901; Morgado & Tanaka 2001: 177; Coelho et al . 2006: 51; Manning & Reed 2006: 289.* Alpheus formosus -a—Knowlton & Mills 1992: 2. Alpheus formosus sp. a—Knowlton et al . 1993: 1630. Alpheus formosus A—Williams et al . 2001: 377. Alpheus formosis (lap. cal.)— McClure 2005: 142, fig. 14, pl. 4, fig. A.* Crangon formosus — Hay & Shore 1918: 384; Schmitt 1924 a: 65; Schmitt 1924 b: 73; Pearse 1932: 107; Schmitt 1935: 144; Schmitt 1936: 368; Schmitt 1939: 28; Pearse 1950: 150; Pearse & Williams 1951: 143.* Crangon formosum — Manter 1933: 177.* Alpheus Poeyi Guérin-Méneville 1857: 19. Alpheus panamensis (not sensu Kingsley 1878)— Pocock 1890: 519; Zimmer 1913: 391; Fausto-Filho 1974: 5.* Not Alpheus formosus — Christoffersen 1979: 315 (part., specimens from E Pacific) (= A. panamensis Kingsley, 1878); Frische 2003: 38 (color photograph, = Alpheus sp.). *Remark: Two species were previously confused under the name “ Alpheus formosus ”; therefore, some of the abovelisted records may actually refer to the new species and not to A. formosus . Type material .— USA, Florida. Neotype, ovig. female (CL 9.7), USNM 1100697, USA, Florida, Big Pine Key, Bahia Honda State Park, shallow subtidal (less than 1.5 m), under rocks, coll. A. Anker, 18 Apr 2004 [fcn 04-010]. Additional material examined.— Panama (Caribbean coast). 1 male (CL 5.6), 1 female (CL 6.0), USNM 1100699, Bocas del Toro, Isla Bastimentos, shallow subtidal (0.5–1 m), from coral rocks, coll. A. Anker, 21 Oct 2005 [fcn 05- 103]; 1 male (CL 7.8) USNM 1100700, Isla Grande, southern shore, shallow subtidal (0.5– 1.5 m), from coral rubble, coll. A. Anker, 21 Apr 2006 [fcn 06- 425]; 1 juvenile (CL not measured), USNM 1100701, Isla Grande, western point, from coral rocks, shallow subtidal (0.5–1m), coll. A. Anker and C. Hurt, 6 Oct 2005 [fcn 05- 101]; 1 male (CL 6.9), USNM 1100702, same collection data as previous specimen [fcn 06- 392]. Costa Rica (Caribbean coast). 3 males (CL 5.8, 6.6, 6.5), 1 ovig. female (CL 6.7), USNM 1100698, Cahuita, shallow subtidal (0.5–1.5 m), from rock crevices and Halimeda clumps, coll. A. Anker, I.S. Wehrtmann and L. Harris, 26–27 Nov 2005 [fcn 05- 100]; 1 male (CL 10.3), MNHN-Na 16385, same collection data as previous specimens [fcn 05- 102]. Aruba. 2 males (CL 5.3, 6.3), 1 female (CL 6.2), 1 ovig. female (CL 7.1), MNHN-Na 16360, Baby Beach, shallow subtidal (1–1.5 m), from crevices in coral rubble, coll. A. Anker, 6 Dec 2003 [fcn 03-011]. Guadeloupe. 1 female (CL not measured), MNHN-Na 13715, Le Moule, depth 2 m, coll. F. Fasquel, 29 Oct 1999; 1 male (CL not measured), MNHN-Na 16386, same collection data as for previous specimen. Brazil. 2 males (CL 6.7, 7.8), 1 ovig. female (CL 7.9), MNRJ 20755, LT 702, Atol das Rocas, between Piscina das Tartarugas and Piscina das Rocas, in pools, among calcareous algae, coll. P.S. Young, P.C. Paiva and A.A. Aguiar, 28 Oct 2000 [1 male dissected]; 1 male (CL 5.7), MNRJ 20756, Atol das Rocas, Piscina do Cemitério, in calcareous algae, coll. P.S. Young et al ., 1 Jan 2001; 1 male (CL 9.5), 1 ovig. female (CL 9.4), MNRJ 20757, Atol das Rocas, near Pedra do Garapira, in tide pool, coll. P.S. Young, P.C. Paiva and A.A. Aguiar, 14 Oct 2000; 1 male (CL 11.0), MNRJ 20758, Atol das Rocas, Piscina das Rocas, in calcareous alga, coll. P.S. Young et al ., 26 Oct 2000; 1 male (CL not measured), MNHN-Na 16359, Pernambuco, Rio Formozo, coll. A.C. Branner Hartt, Dec 1875 [specimen lacking all pereiopods]. USA, Florida. 1 male (CL 11.5), OUMNH-ZC 2007 - 13 -034, USA, Florida, near Marineland, 5 km south of Sebastian Inlet, shallow subtidal, coll. J.A. Baeza, 15 Jul 2007 [fcn 07- 240; specimen somewhat dessicated during transport, rehydrated in EtOH]. British Virgin Islands. 1 juvenile (CL not measured), Guana Island, coll. Guana Marine Invertebrate Project, 2000 [fcn Vc 0600] [specimen missing minor cheliped, identification tentative based on length of adrostral furrows; specimen will be deposited in LACM]. Redescription .—Carapace glabrous, non-setose, somewhat compressed laterally. Rostrum well developed, dorsally flattened; margins fringed with setae directed up- or sidewards (Fig. 1 a, b); tip acute, reaching to or slightly beyond distal margin of first segment of antennular peduncle (Fig. 1 a); rostral carina absent; orbito-rostral process broad, round W-shaped. Orbital hoods with acute teeth inserted at some distance from anterior margin (Fig. 1 a). Adrostral furrows deep, narrow, abruptly delimited from rostrum, posteriorly extending almost to level of cornea base (Fig. 1 a). Pterygostomial angle rounded, somewhat protruding anteriorly (Fig. 1 b, c); cardiac notch well developed. Eyes completely concealed in dorsal, lateral and partly in frontal view. Ocellar beak vertically protruding towards rostrum, more or less visible in lateral view (Fig. 1 c). Antennular peduncles relatively stout, second segment longer than dorsally visible portion of first, about 1.5 times as long as wide (Fig. 1 a); stylocerite with acute tip, slightly overreaching distal margin of first segment (Fig. 1 a, b); mesioventral carina of first segment with large, bluntly protruding tooth (Fig. 1 c); lateral flagellum with numerous tufts of aesthetascs, accessory ramus rudimentary (Fig. 1 b). Antenna with stout basicerite bearing strong acute ventrolateral tooth, its tip not reaching level of stylocerite tip (Fig. 1 b); carpocerite stout, reaching slightly beyond distolateral spine of scaphocerite; scaphocerite with very strong distolateral tooth separated from narrow blade by deep cleft (Fig. 1 a), tip of distolateral tooth reaching far beyond blade and exceeding end of antennular peduncle (Fig. 1 a); lateral margin of scaphocerite very slightly concave at mid-length (Fig. 1 a). Mouthparts (mandible, maxillule, maxilla, first and second maxillipeds) typical for Alpheus . Third maxilliped moderately stout; coxa with distally subacute lateral plate; exopod reaching penultimate segment; antepenultimate segment slightly flattened, ventral margin straight; penultimate segment about 2.5 times as long as wide; arthrobranch well developed (third maxilliped generally very similar to that of A. panamensis , cf. Kim & Abele, 1988: fig. 15 d, and to that of below-described new species, cf. Fig. 5 d). Male major cheliped (Fig. 2) with short, stout ischium; merus stout, about 2.5 times as long as wide proximally, dorsal margin distally protruding (Fig. 2 a, c); ventrolateral margin straight, ventromesial margin rugose, with spinules, distally with acute tooth (Fig. 2 c); carpus very short, cup-shaped; chela large, subcylindrical, broadly oval in cross-section; palm smooth, moderately setose distally; distomesial margin with strong acute tooth (Fig. 2 b); linea impressa conspicuous (Fig. 2 a); adhesive discs relatively large (Fig. 2 a); fingers more than half-length of palm, dactylus usually reaching beyond pollex, with large plunger, latter distally with stamen-shaped sensillae (Fig. 2 a). Female major cheliped similar to that of male, except for somewhat smaller size and different proportions of fingers to palm (Fig. 4 b). Mesiodistal tooth on merus sometimes (Fig. 4 b, c), independently of sex, with two acute teeth: one larger and stronger tooth, and one much smaller tooth. Male minor cheliped (Fig. 3) with short, stout ischium; merus about three times as long as wide proximally; ventrolateral margin straight; ventromesial margin somewhat rugose, usually with spinules; distally with acute tooth (Fig. 3 d); carpus cup-shaped; chela smooth, ovate in cross-section, somewhat setose mesially (Fig. 3 b); distomesial margin of palm with strong acute tooth (Fig. 3 a, b); linea impressa conspicuous (Fig. 3 a); adhesive discs small (Fig. 3 a); fingers about as long as palm, with well developed rows of balaeniceps setae (Fig. 3 a–c), tips strongly curved, crossing when chela closed. Female minor cheliped similar to that of male; chela with well developed rows of balaeniceps setae (Fig. 4 d). Second pereiopod with ischium subequal to merus (Fig. 1 d); carpus five-segmented, ratio of carpal segments (from proximal to distal) approximately: 6 / 3 / 1.5 / 1.5 / 3 (Fig. 1 d); chela simple, with fingers slightly longer than palm. Third pereiopod with ischium bearing small ventrolateral spine (Fig. 1 e); merus unarmed, about six times as long as wide; carpus unarmed; propodus with stout spines or pairs of spines along ventral margin and two spines distoventrally near articulation with dactylus (Fig. 1 e); dactylus about 1 / 3 propodus length, simple, conical, gradually curved towards acute tip, with some setae (Fig. 1 e). Fourth pereiopod similar to third pereiopod. Fifth pereiopod smaller and slenderer than third and fourth pereiopods; ischium unarmed; propodus with row of spines and at least eight rows of grooming setae distolaterally; dactylus conical, as in third pereiopod. Abdominal pleura with posteroventral margins broadly rounded; sixth somite without articulated flap, dorsolateral projections on each side of telson bluntly rounded. Male second pleopod with appendix masculina reaching somewhat beyond appendix interna, with numerous slender apical and subapical setae. Uropod with protopod bearing elongate acute distolateral tooth (Fig. 1 f); exopod with strong acute distolateral tooth adjacent to distolateral spine; diaeresis bearing strong lateral tooth, mesial to distolateral spine (Fig. 1 f, g); distolateral spine stout, usually black to tan-brown (Figs. 4 e, 7 e), sometimes pale in alcohol (Fig. 1 f, g); distal margins of endopod with row of spinules (Fig. 1 g). Telson moderately broad, subrectangular, tapering towards posterior margin (Fig. 1 f); dorsal surface without median groove, with two pairs of strong dorsal spines, situated at some distance from lateral margins, both pairs situated in posterior 2 / 3 length of telson (Fig. 1 f); posterior margin convex centrally, with two pairs of posterolateral spines, mesial being much longer than lateral (Fig. 1 f); anal tubercles well developed. Gill formula typical for Alpheus . Size .—The largest Caribbean specimen is a male from Cahuita, Costa Rica, with CL 10.3 mm and TL 33.5 mm; the CL of remaining adult specimens range from 5.3 mm to 7.8 mm. The CL of the neotype (ovigerous female) from Florida Keys is 9.7 mm; the maximum CL of Florida specimens was 14.7 mm (Hendrix 1971). The largest specimen from Brazil is a male from Atol das Rocas with 11.0 mm CL and 35.7 mm TL. Color pattern .—Body red-brown to purple-brown, with more or less intense yellow mediodorsal band extending from rostrum tip to posterior margin of sixth abdominal somite; carapace with white lateral band extending from anterolateral margin to cardiac notch, continued by zigzag white band ending at sixth abdominal somite; rostrum entirely yellow, usually not bordered by reddish brown on margins; carapace flanks below white band pale; telson and uropods red-brown with large yellow patches and spots; walking legs and second pereiopods bluish, sometimes intense magenta blue; antennular peduncles yellow-brown; antennal scaphocerite brown with white areas, flagella pale bluish; chelipeds pale brown to intense orange brown, major chela with pale patch near articulation with dactylus; dactylus and pollex distally pinkish; minor chela mostly pale brown to orange brown (Fig. 7 c–e); distolateral spine on uropdal exopod usually brown to almost black (Fig. 7 e); eggs orange-reddish (Fig. 7 d). Ecology .—Intertidal to about 40 m (Sterrer 1986), commonly associated with reef-fringing habitats, in crevices of rocks, dead and living corals and coral rubble (Verrill 1922; present study); mixed sand-rubble bottoms among turtle grass ( Thalassia testudinum ), under rocks and coral rubble; in crevices on reefs of the sabellariid polychaete Phragmatopoma sp. (Camp et al . 1977; Gore et al . 1978); in empty conch shells ( Strombus ) on the outer fringing reefs near Thalassia beds (Hendrix 1971); occasionally in sponges, e.g., Callyspongia , Ircinia (Pearse 1950; Chace 1956), among bryozoan colonies, Schizoporella sp. (Christoffersen 1979; Morgado & Tanaka 2001), and in living corals, e.g., Oculina and Porites (Chace 1972; Reed et al . 1982); occasionally entering sea-connected cave systems (Hobbs 1998). Type locality .—Key West, Florida (Gibbes 1850). Distribution .—Western Atlantic: North Carolina (Hay & Shore 1918; Williams 1965, 1984; Christoffersen 1979); reefs of South Carolina (Pearse & Williams 1951); Florida: southern and central-eastern Florida (e.g., Fort Pierce, Sainte-Lucie, Hutchinson Island, Sebastian Inlet), Florida Keys (e.g., Key West, Big Pine Key, Cedar Key), Dry Tortugas (Gibbes 1850; Coutière 1910; Zimmer 1913; Balss 1924; Boone 1930; Pearse 1932; Hendrix 1971; Camp et al . 1977; Gore et al . 1978; Reed et al . 1982; Posey et al . 1998; present study); Bermuda (Heilprin 1888; Verrill 1922; Sterrer 1986); US Virgin Islands (Hendrix 1971); St. John (Zimmer 1913); British Virgin Islands: Guana (present study); Bahamas: Bimini, Cay Sal Bank (Pearse 1950; Lemaitre 1984), Blue Holes Cave System (Hobbs 1998); Puerto Rico; Culebra (Rathbun 1901; Schmitt 1935; Ray 1974); French Antilles: Martinique, Guadeloupe (Carvacho 1982; present study); Tobago (Chace 1972); Barbados (Zimmer 1913; Schmitt 1924 b); Netherlands Antilles: Aruba, Curaçao, Bonaire (Schmitt 1924 a, 1936); present study); Venezuela: Los Roques, Tucacas, Isla Margarita, Arrecifes (Chace 1956; Rodríguez 1980; Rodríguez 1986); Colombia: Providencia (Schmitt 1939); Panama: Isla Grande, Colón, Bocas del Toro (Abele 1976; Cubit & Williams 1983; present study); Costa Rica: Limón, Cahuita (Vargas & Cortés 1999; present study); Honduras: Utila (A. Anker, pers. obs.); Mexico: Quintana Roo (Chace 1972), Veracruz, Campeche (Hernández-Aguilera et al . 1996), Puerto Morelos, Punta Estrella (Markham et al . 1990); Jamaica: Kingston (Zimmer 1913); Cuba: Gulf of Batabano (Martínez-Iglesias et al . 1996, 1997); Brazil: Natal, Rio Grande do Norte, Pernambuco, Alagoas, Bahia (including Abrolhos Islands), Ceara, Espirito Santo, Rio de Janeiro, São Paulo (Rathbun 1900; Fausto-Filho 1970; Corrêa 1972; Christoffersen 1979, 1998; Coelho et al . 2006), Fernando do Noronha (Pocock 1890); Atol das Rocas (present study). Some of the above-listed literature records may actually refer to the below-described new species, and not to A. formosus , as the two species were not distinguished in the past. Remarks .— Alpheus formosus is closely related to A. panamensis but can be distinguished from the latter by the orbitorostral grooves extending to the level of eye base posteriorly (vs. to the base of the orbital hoods in A. panamensis ); the rostral plate being slightly narrower at base; and the usually much darker distolateral spine on the uropod (black in A. formosus vs. pale, distally tan in A. panamensis ) (see also Kim & Abele 1988). The color of the uropodal spine may be lighter if the animal has recently molted. For instance, some alcohol-preserved specimens from Atol das Rocas, including the illustrated male specimen, have a pale spine, without trace of black pigment (Fig. 1 f). Most individuals, however, including the neotype, have a dark brown to blackish spine in life and in alcohol (Fig. 4 e). Alpheus formosus can be distinguished from the below-described new species by the presence of balaeniceps setae on the fingers of the minor chela in both sexes (more developed in males), the posteriorly more extending orbitorostral grooves and several features of the color pattern (see below). GenBank number .— EF 532605 (fcn 98-163), EF 532606 (fcn 98-189), EF 532607 (fcn 98-190), EF 532608 (fcn 05- 101, USNM 1100701), EF 532609 (fcn 06- 414), EF 532610 (06- 499), AF 309903, AF 309904. : Published as part of Anker, Arthur, Hurt, Carla & Knowlton, Nancy, 2008, Revision of the Alpheus formosus Gibbes, 1850 complex, with redescription of A. formosus and description of a new species from the tropical western Atlantic (Crustacea: Decapoda: Alpheidae), pp. 1-22 in Zootaxa 1707 on pages 5-12, DOI: 10.5281/zenodo.180922 : {"references": ["Gibbes, L. R. (1850) On the carcinological collections of the cabinets of natural history in the United States: with an enumeration of the species contained therein and descriptions of new species. Proceedings of third meeting of American Association for Advancement of Science, 3, 165 - 201.", "Kingsley, J. S. (1878 a) A synopsis of North American species of the genus Alpheus, VII. Bulletin of the United States Geological and Geographical Survey, 4, 189 - 199.", "Heilprin, A. (1888) Contributions to the natural history of the Bermuda Islands (incl. Crustacea). Proceedings of the Academy of Natural Sciences of Philadelphia, 1888, 302 - 328.", "Heilprin, A. (1889) The Bermuda Islands: A contribution to the physical history and zoology of the Somers Archipelago. With an examination of the structure of coral reefs. Researches undertaken under the auspices of the Academy of Natural Sciences of Philadelphia, 1 - 231, pls. 1 - 17. Heilprin, Philadelphia.", "Coutiere, H. (1899) Les \" Alpheidae \", morphologie externe et interne, formes larvaires, bionomie. Annales des Sciences Naturelles, Zoologie, serie 8, 9, 1 - 560, pls. 1 - 6. Masson et Cie Ed., Paris.", "Chace, F. A. Jr. & Forest, J. (1970) Henri Coutiere: son oeuvre carcinologique, avec un index pour son memoire de 1899 sur les Alpheidae. Bulletin du Museum national d'Histoire naturelle, serie 2, 41, 1459 - 1486.", "Coutiere, H. (1910) The snapping shrimps (Alpheidae) of the Dry Tortugas, Florida. Proceedings of the United States National Museum, 37, 485 - 487.", "Verrill, A. E. (1900) Additions to the Crustacea & Pycnogonida of the Bermudas. Transactions of the Connecticut Academy of Arts and Sciences, 10, 573 - 582.", "Rathbun, M. J. (1900) The decapod and stomatopod Crustacea, Part I. In: Results of the Branner-Agassiz Expedition to Brazil. Proceedings of the Washington Academy of Sciences, 2, 133 - 156, pl. 8.", "Rathbun, M. J. (1901) The Brachyura and Macrura of Puerto Rico. United States Fish Commission Bulletin, 20, 1 - 137, pls. 1, 2.", "Verrill, A. E. (1922) Decapod Crustacea of Bermuda. Part II. Macrura. Transactions of the Connecticut Academy of Arts and Sciences, 26, 1 - 179, pls. 1 - 48.", "Balss, H. (1924) Westindische Decapoden. Zoologischer Anzeiger, 61, 177 - 182.", "Boone, L. (1930) Crustacea: Anomura, Macrura, Schizopoda, Isopoda, Amphipoda, Mysidacea, Cirripedia, and Copepoda. In: Scientific Results of Cruises of the yachts \" Eagle \" and \" Ara \", 1921 - 1928, William K. Vanderbilt Commanding. Bulletin Vanderbilt Marine Museum, 3, 1 - 221, pls. 1 - 83.", "Chace, F. A. Jr. (1956) Crustaceos decapodos y estomatopodos del Archipielago de los Roques y Isla de la Orchila. In: Mendez, A. et al. (eds.), Archipielago de Los Roques y la Orchila, pp. 145 - 168, 4 pls. Sociedad de Ciencias Naturales La Salle, Editorial Sucre, Caracas.", "Hazlett, B. A. (1962) Aspects of the biology of the snapping shrimp (Alpheus and Synalpheus). Crustaceana, 4, 82 - 83.", "Bullis, H. R. & Thompson, J. R. (1965) Collections by the exploratory fishing vessels Oregon, Silver Bay, Combat and Pelican made during 1956 - 1960 in the Southwestern North Atlantic. Special Scientific Report of the United States Fish and Wildlife Service, Fisheries, 510, 1 - 130.", "Williams, A. B. (1965) Marine decapod crustaceans of the Carolinas. Fishery Bulletin of the U. S. Fish and Wildlife Service, 65, 1 - 298.", "Fausto-Filho, J. (1970) Quarta contribuicao ao inventario dos crustaceos decapodos do nordeste brasileiro. Arquivos de Ciencias do Mar, 10, 55 - 60.", "Hendrix, G. Y. (1971) A systematic study of the genus Alpheus (Crustacea: Decapoda: Alpheidae) in South Florida. PhD Dissertation, University of Miami, Coral Gables, Florida, USA. 184 pp., 24 pls.", "Chace, F. A. Jr. (1972) The shrimps of the Smithsonian-Bredin Caribbean expeditions with a summary of the West Indian shallow-water species (Crustacea: Decapoda: Natantia). Smithsonian Contributions to Zoology, 98, i - x + 1 - 179.", "Correa, M. M. G. (1972) Contribuicao ao conhecimento da fauna do Arquipelago de Abrolhos, Bahia, Brasil. 2. Lista preliminar dos crustaceos decapodos. Boletim de Museu de Historia Natural, Universidade Federal de Minas Gerais, zoologia, 15, 1 - 19 [not seen].", "Coelho, P. A. & Ramos, M. A. (1972) A constituicao e a distribuicao da fauna de decapodos do litoral este da America do Sul entre as latitudes de 5 \u00b0 N e 39 \u00b0 S. Trabalhos Oceanograficos da Universidade Federal do Pernambuco, Recife, 13, 133 - 236.", "Ray, J. P. (1974) A study of the coral reef crustaceans (Decapoda and Stomatopoda) of two Gulf of Mexico reef systems: West Flower Garden, Texas and Isla de Lobos, Veracruz, Mexico. PhD Dissertation. Texas A & M University, College Station, Texas. 323 pp.", "Camp, D. K., Whiting, N. H. & Martin, R. E. (1977) Nearshore marine ecology at Hutchinson Island, Florida: 1971 - 1974. V. Arthropods. Florida Marine Research Publication, 25, 1 - 63.", "Gore, R. H., Scotto, L. E. & Becker, L. J. (1978) Community composition, stability, and trophic partitioning in decapod crustaceans inhabiting some subtropical sabellariid worm reefs. Studies on decapod Crustacea from the Indian River region of Florida. IV. Bulletin of Marine Science, 28, 221 - 248.", "Christoffersen, M. L. (1979) Decapod Crustacea: Alpheoidea. Campagnes de la Calypso au large des cotes atlantiques de l'Amerique du Sud (1961 - 1962). I. Resultats Scientifiques de la Campagne de la Calypso, 11, 297 - 377.", "Corredor, L., Criales, M. M., Palacio, J., Sachez, H. & Werding, B. (1979) Decapodos colectados en las islas del Rosario. Anales del Instituto de Investigaciones Marinas de Punta Betin, 11, 31 - 34. [not seen]", "Christoffersen, M. L. (1980 a). Taxonomia e distribuicao geografica dos Alpheoidea (Crustacea, Decapoda, Natantia) do Brasil, Uruguay e norte da Argentina, incluindo consideracoes sobre a divisao do sul do continente em provincias biogeograficas marinhas. PhD Thesis, Universidade de Sao Paulo, Sao Paulo, 467 pp.", "Christoffersen, M. L. (1980 b) Distribuicao vertical de alguns Alpheidae (Crustacea, Caridea) na regiao entremares do sul do Brasil. Abstracts VIII Congresso Brasileiro de Zoologia, Brasilia, pp. 39 - 40.", "Rodriguez, G. (1980) Crustaceos decapodos de Venezuela. Instituto Venezolano de Investigaciones Cientificas, Caracas, 494 pp.", "Fausto-Filho, J. (1980) Crustaceos estomatopodos e decapodos dos substratos de cascalho do nordeste brasileiro. Arquivos de Ciencias do Mar, 20, 101 - 124.", "Morgado, E. H. (1980) A endofauna de Schizoporella unicornis (Johnston, 1847) no litoral norte do estado de Sao Paulo. MSc thesis, Universidade Estadual de Campinas, Campinas, Brazil. [not seen]", "Reed, J. K., Gore, R. H., Scotto L. E. & Wilson, K. A. (1982) Community composition, structure, areal and trophic relationships of decapods associated with shallow and deep-water Oculina varicosa coral reefs. Studies on decapod crustacea from the Indian River Region of Florida, XXIV. Bulletin of Marine Science, 32, 761 - 786.", "Carvacho, A. (1982) Sur une petite collection de crevettes de la Martinique. Caribbean Journal of Science, 17, 15 - 20.", "Cubit, J. & Williams, S. (1983) The invertebrates of Galeta Reef (Caribbean Panama): a species list and bibliography. Atoll Research Bulletin, 269, 1 - 45.", "Williams, A. B. (1984) Shrimps, lobsters and crabs of the Atlantic Coast of the eastern United States, Maine to Florida. Smithsonian Institution Press, Washington DC, 550 pp.", "Lemaitre, R. (1984) Decapod crustaceans from Cay Sal Bank, Bahamas, with notes on their zoogeographic affinities. Journal of Crustacean Biology, 4, 425 - 447.", "Young, P. S. (1984) Analise qualitativa e quantitativa da fauna associada aos corais hermatipicos Mussismilia hartii, M. hispida e Siderastrea stellata (Coelenterata: Scleractinia) nos recifes de Joao Pessoa, PB. M. Sc. Thesis, Universidade Federal da Paraiba, Joao Pessoa, 120 pp. [not seen]", "Freitas-Lins, H. M. de L. (1985) Distribuicao espacial de alguns decapodos e estamatopodos (Crustacea, Malacostraca) nas pontas rochosas do Cabo Branco e Tambau, Joao Pessoa, PB. M. Sc. Thesis, Universidade Federal da Paraiba, Joao Pessoa, 89 pp. [not seen]", "Young, P. S. (1986) Analise qualitativa e quantitativa da fauna associada a corais hermatipicos (Coelenterata, Scleractinia) nos recifes de Joao Pessoa, PB. Revista Brasiliera de Biologia, 46, 99 - 126.", "Sterrer, W. (1986) Marine fauna and flora of Bermuda. A systematic guide to the identification of marine organisms. John Wiley & Sons, 742 pp., 16 pls.", "Rodriguez, B. (1986) Los camarones (Crustacea; Decapoda; Natantia) del Parque Nacional Archipielago de los Roques. Trabajo especial de grado para optar al titulo de Licenciado en Biologia, Universidad Central de Venezuela, Caracas. 350 pp.", "Abele, L. G. & Kim, W. (1986) An illustrated guide to the marine decapod crustaceans of Florida. Technical Series, Department of Environmental Regulations, 8, parts 1 and 2, 760 pp.", "Kim, W. & Abele, L. G. (1988) The snapping shrimp genus Alpheus from the eastern Pacific (Decapoda: Caridea: Alpheidae). Smithsonian Contributions to Zoology, 454, 1 - 119.", "Marquez, M. J. G. (1988) Los camarones carideos (Crustacea, Decapoda, Caridea) de las Islas Cubagua y Margarita, Venezuela. Trabajo de grado presentado para optar al Titulo de Licenciado en Biologia, Mencion Biologia Marina. Cumana, 1988, 127 pp.", "Markham, J. C., Donath-Hernandez, F. E., Villalobos-Hiriart, J. L. & Diaz-Barriga, A. C. (1990) Notes on the shallow water marine Crustacea of the Caribbean coast of Quintana Roo, Mexico. Anales del Instituto de Biologia, Universidad Nacional Autonoma de Mexico, zoologia, 61, 405 - 446 [not seen].", "Martinez-Iglesias, J. C., Carvacho, A. & Rios, R. (1996) Catalogo de los carideos marinos (Crustacea, Decapoda, Caridea) de las aguas someras de Cuba. Avicennia, 4 / 5, 27 - 40.", "Hernandez Aguilera, J. L., Toral Almazan, R. E. & Ruiz Nuno, J. A. (1996) Especies catalogadas de crustaceos estomatopodos y decapodos para el Golfo de Mexico, Rio Bravo, Tamps. a Progreso, Yuc. Direccion de Oceanografia, Direccion General de Oceanografia Naval, Secretaria de Marina, Mexico, i - xiii, 1 - 132.", "Martinez-Iglesias, J. C., Rios, R. & Carvacho, A. (1997) Las especies del genero Alpheus (Decapoda: Alpheidae) de Cuba. Revista de Biologia Tropical, 44 / 45, 401 - 429.", "Hobbs, H. H. III. (1998) Decapoda (Caridea, Astacidea, Anomura): In Juberthie, C. and Decu, V. (eds.), Encyclopdia Biospeologica, Vol. II, pp. 891 - 911. Societe de Biospeologie, Paris.", "Santos, M. A. C. dos & Coelho, P. A. (1998) Camaroes (Crustacea, Decapoda) do litoral de Jaboatao dos Guararapes, Pernambuco - Brasil. Trabalhos Oceanograficos da Universidade Federal do Pernambuco, Recife, 26, 63 - 83.", "Posey, M. H., Troy, D. A., Banner, S., Vose, F. & Lindberg, W. (1998) Temporal variability, diversity and guild structure of a benthic community in the notheastern Gulf of Mexico. Bulletin of Marine Science, 63, 143 - 155.", "Christoffersen, M. L. (1998) Malacostraca. Eucarida. Caridea, Crangonoidea and Alpheoidea (except Glyphocrangonidae and Crangonidae). In Young, P. S. (ed.), Catalogue of Crustacea of Brazil, pp. 351 - 372. Museu Nacional, Rio de Janeiro.", "Vargas, R. & Cortes, J. (1999) Biodiversidad marina de Costa Rica: Crustacea: Decapoda (Penaeoidea, Sergestoidea, Stenopodidea, Caridea, Thalassinidea, Palinura) del Caribe. Revista de Biologia Tropical, 47, 887 - 911.", "Morgado, E. H. & Tanaka, N. O. (2001) The macrofauna associated with the bryozoan Schizoporella errata (Walters) in southeastern Brazil. Scientia Marina, 65, 173 - 181.", "Coelho, P. A., de Almeida, A. O., de Souza-Filho, J. F., Bezerra, L. E. A. & Giraldes, B. W. (2006) Diversity and distribution of the marine and estuarine shrimps (Dendrobranchiata, Stenopodidea and Caridea) from North and Northeast Brazil. Zootaxa, 1221, 41 - 62.", "Manning, R. B. & Reed, K. (2006) Decapod crustaceans deposited in the zoological museum of Copenhagen by William Stimpson in 1859. Raffles Bulletin of Zoology, 54, 283 - 293.", "Knowlton, N. & Mills D. K. (1992) The systematic importance of color and color pattern: evidence for complexes of sibling species of snapping shrimp (Caridea: Alpheidae: Alpheus) from the Caribbean and Pacific coasts of Panama. Proceedings of the San Diego Society of Natural History, 18, 1 - 5.", "McClure, M. (2005) Alpheidae. In: Hernandez Aguilera, J. L., Ruiz Nuno, J. A., Toral Almazan, R. E. & Arenas Fuentes, V. (eds.), Camarones, langostas y cangrejos de la costa este de Mexico. Volume 1, pp. 119 - 202. Estudio y Conservacion de la Naturaleza, A. C. y CONABIO, Mexico. 350 pp, pls. 1 - 8.", "Hay, W. P. & Shore, C. A. (1918) The decapod crustaceans of Beaufort, North Carolina, and surrounding regions. Bulletin of Bureau of Fisheries, Washington, 35, 371 - 475, pls. 25 - 39.", "Schmitt, W. L. (1924 b) Report on Macrura, Anomura and Stomatopoda collected by the Barbados-Antigua Expedition from the University of Iowa in 1918. Studies of Natural History, Iowa University, 10, 65 - 99, pls. 1 - 5.", "Pearse, A. S. (1932) Observations on the parasites and commensals found associated with crustaceans and fishes at Dry Tortugas, Florida. Papers from the Tortugas Laboratory, Carnegie Institution of Washington, 28, 103 - 115.", "Schmitt, W. L. (1935) Crustacea Macrura and Anomura of Porto Rico and the Virgin Islands. Science Survey of Porto Rico (New York Academy of Sciences), 15, 125 - 227.", "Schmitt, W. L. (1936) Macruran and anomuran Crustacea from Bonaire, Curacao and Aruba. Zoologische Ergebnisse einer Reise nach Bonaire, Curacao und Aruba im Jahre 1930. Nr 16. Zoologische Jahrbucher, Abteilung fur Systematik, Oekologie und Geographie der Tiere, 67, 363 - 378, pls. 11 - 13.", "Schmitt, W. L. (1939) Decapod and other Crustacea collected on the Presidential Cruise of 1938 (with introduction and station data). Smithsonian Miscellaneous Collections, 98, 1 - 29, 3 pls.", "Pearse, A. S. (1950) Notes on the inhabitants of certain sponges at Bimini. Ecology, 31, 149 - 151.", "Pearse, A. S. & Williams, L. G. (1951) The biota of the reefs off the Carolinas. Journal of Elisha Mitchell Scientific Society, 67, 133 - 161.", "Manter, W. H. (1933) The genus Helicometra and related trematodes from Tortugas, Florida. Papers from the Tortugas Laboratory, Carnegie Institution of Washington, 28, 169 - 180, 3 pls.", "Guerin-Meneville, F. E. (1857) Crustaces. Animaux articules a pieds articules. In: de la Sagra, R. (ed.), Histoire physique, politique et naturelle de l'ile de Cuba, pp. 1 - 87, pl. 2.", "Pocock, R. I. (1890) Crustacea. In: Ridley, H. N. (ed.), Notes on the zoology of Fernando Noronha. Journal of the Linnean Society, Zoology, 20, 506 - 526.", "Zimmer, C. (1913) Westindische Decapoden, 1: Die Familie Alpheidae. Zoologische Jahrbucher, Supplement 11, 381 - 412.", "Fausto-Filho, J. (1974) Stomatopod and decapod crustaceans of the Archipelago of Fernando do Noronha, northeast Brazil. Arquivos de Ciencias do Mar, 14, 1 - 35.", "Frische, J. (2003) Garnelen und Krebse im Meerwasseraquarium. Bede-Verlag, Ruhmannsfelden, 79 pp."]}